Nitrogen use efficiency trends for sustainable crop productivity in Lake Victoria basin: smallholder farmers' perspectives on nitrogen cycling. (27th January 2022) - Ntinyari, Winnie; Gweyi-Onyango, Joseph; Giweta, Mekonnen; Mochoge, Benson; Mutegi, James; Nziguheba, Generose; Masso, Cargele
Abstract: Nitrogen Use Efficiency (NUE) is one of the established metrics for benchmarking management of Nitrogen (N) in various systems. Numerous approaches to calculate NUE exist, making it difficult to compare the performances of systems depending on the methodology used. This study adopted the conceptualized framework by European Union Nitrogen Expert Panel (EUNEP) to calculate NUE values for cereal crops to determine future trends for the first time in the Lake Victoria region. Data were collected through in-person interviews among maize and rice smallholder farmers within the Lake Victoria region. A total of 293 observations were recorded. Collected data on yield and N fertilizer were used to make projections on the changes of NUE based on scientific and policy recommendations for Sub-Saharan Africa for 2020 (base year), 2025, 2030, and 2050. Significant differences in maize grain yield for both fertilized and unfertilized farms were observed with very low yields of 2.4 t ha −1 (fertilized) and 1.4 t ha −1 (unfertilized). The graphical representation of NUE of both maize and rice showed that most farmers were in the zone of soil N mining. Projected results showed that most maize farmers within Lake Victoria region will continue to experience NUE values >90%, low N inputs <50 kg N ha −1 ) and less than 5 t ha −1 maize crop yield over the years. For rice farmers, Nyando and Nzoia catchments had surpassed the set target of both yield (6 t ha −1 ) and N input (50 kg N ha −1 ). However, NUE values remain higher than the optimal ranges of 50%–90% (127.14%−267.57%), indicating risks of depleting soil N status. The unbalanced N fertilization also showed a trend below the linear neutrality option and the average N output for good N management for both crops. Therefore, farmers need to explore various crop management options that could increase N use efficiencies. This should be coupled with policies that promote farmers to access more N input and advocate for optimal management of N and improved quality of the cereals.